2014
DOI: 10.2478/johh-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

Synergic hydraulic and nutritional feedback mechanisms control surface patchiness of biological soil crusts on tertiary sands at a post-mining site

Abstract: Abstract:In a recultivation area located in Brandenburg, Germany, five types of biocrusts (initial BSC1, developed BSC2 and BSC3, mosses, lichens) and non-crusted mineral substrate were sampled on tertiary sand deposited in [1985][1986] to investigate hydrologic interactions between crust patches. Crust biomass was lowest in the non-crusted substrate, increased to the initial BSC1 and peaked in the developed BSC2, BSC3, the lichens and the mosses. Water infiltration was highest on the substrate, and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Though this is not a universal model for dryland soil succession and surface component distribution generalizable to all areas, similar patterns have been observed in other regions with different climate conditions and soil properties (Kidron et al, 2010;Fischer et al, 2014;Durham et al, 2018). For example, Kidron et al (2010) found that in undisturbed areas in the Negev, cyanobacteria-dominated biocrusts predominated on the sunniest hillslopes, whereas lichen and mosses were more frequent in shaded areas with longer wet periods.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Though this is not a universal model for dryland soil succession and surface component distribution generalizable to all areas, similar patterns have been observed in other regions with different climate conditions and soil properties (Kidron et al, 2010;Fischer et al, 2014;Durham et al, 2018). For example, Kidron et al (2010) found that in undisturbed areas in the Negev, cyanobacteria-dominated biocrusts predominated on the sunniest hillslopes, whereas lichen and mosses were more frequent in shaded areas with longer wet periods.…”
Section: Discussionsupporting
confidence: 59%
“…These specific adaptations facilitate their survival, even under very dry conditions, as observed in many other places (Kidron et al, 2010;Dojani et al, 2011;Patzelt et al, 2014). Other studies in more mesic environments have found that higher cyanobacterial concentrations in depositional areas are related to the strong resilience of these organisms to salinity stress, as water and salt redistribution by runoff from hillslopes to these areas tend to concentrate salts on the surface (Fischer et al, 2014). Other studies in more mesic environments have found that higher cyanobacterial concentrations in depositional areas are related to the strong resilience of these organisms to salinity stress, as water and salt redistribution by runoff from hillslopes to these areas tend to concentrate salts on the surface (Fischer et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is the principal rationale for the Hortonian flow that takes place in arid and semiarid regions (Horton, ). Pore clogging was also shown to determine run‐off from biocrusts (Fischer, Gypser, Subotina, & Veste, ; Fischer, Veste, Wiehe, & Lange, ; Kidron et al, ; Verrecchia, Yair, Kidron, & Verrecchia, ). The notion that soil pores, that is, subsurface pores (especially macro pores) determine infiltration on biocrusted surfaces, is however highly questionable.…”
Section: Common Paradigmsmentioning
confidence: 99%
“…Research into biocrust disturbance and recovery post-mining is rare (see Fischer et al, 2014;Lukešová, 2001;Mazor et al, 1996;Setyawan et al, 2016), yet there is a real need for focus on practical approaches that contribute to the restoration of soil 10 function and measure relevant aspects of success through soil microbial communities (Harris, 2003;Tongway and Hindley, 2004). Mine rehabilitation is a complex process that involves many levels of understanding of difficult issues relating to ecosystem function where the removal or burial of the bioactive soils can have knock-on effects for rehabilitation efforts such as native seedling establishment.…”
Section: Introductionmentioning
confidence: 99%